Health care seeking behaviour among caregivers of children with pneumonia in a rural area. - Kamaruzaman, Nor Azam; Muthupalaniappen, Leelavathi; Pasi, Hafizah (Japan International Cultural Exchange Foundation & Japan Health Sciences University, 2013)
Objective: The aim of this study is to evaluate caregiver's health seeking behaviour for children with pneumonia and to determine the associated factors.